PENGARUH IMPOR PANGAN TERHADAP KESEJAHTERAAN PETANI PANGAN - Martha Carolina; Robby A. Sirait (Pusat Kajian Anggaran, 2018)
This study uses Feasible Generalized Least Square (FLGS) model to assess the impact of food import on the farmers welfare by monthly time series data for the period 2011 to 2017. The number of food imports were used as dependent variables and independent variables is Nilai Tukar Petani (NTP) as indicator of farmers welfare degree. The estimation showed a negative relationship between the number of food import and farmers welfare. But, the relationship not statistically significant.